IMPLEMENTASI PROGRAM BIMBINGAN DAN KONSELING BAGI PENGEMBANGAN SELF-ESTEEM ANAK USIA SD/MI - Hidayat, Hidayat (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Self-esteem is an important component and should be present in a child. With the self-esteem in children, the spirit of enthusiasm and self motivation in children will present itself. Improve self-esteem in children ought to be used as an early reflection of the parents, because many things can happen when children feel powerless or inferior. In addition to the family, school is the child's immediate environment. For that schools have to provide personal guidance programs, social services are administered by the guidance and counseling program. School elements are closely associated with the development of self-esteem of children is especially homeroom teacher. Given the importance of self-esteem in the optimization of child development, for it in this article will be described in detail discussion on the matter.